Let’s Talk about Digital Learners in the Digital Era - Gallardo-Echenique, Eliana Esther; Marqués-Molías, Luis; Bullen, Mark; Strijbos, Jan-Willem (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
This paper reports on a literature review of the concept of “Digital Natives” and related terms. More specifically, it reports on the idea of a homogeneous generation of prolific and skilled users of digital technology born between 1980 and 1994. In all, 127 articles published between 1991 and 2014 were reviewed. On the basis of the findings, there appears to be no commonly-accepted definition of a “Digital Native”. The concept varies among individuals, societies, regions and nations, and also over time. Moreover, there are a number of variables other than age that may help us understand the nature of students’ use of digital technologies. The so-called “Digital Native” literature demonstrates that despite students’ high digital confidence and digital skills, their digital competence may be much lower than those of their “digital teachers”. Given the confusion surrounding “Digital Native” and its affiliates, we propose to unify them under the concept “digital learners”.